Validasi Eksperimental dan Teoritis Daya Dukung Tiang PVC dengan Metode Mazurkiewicz dan Mayerhof - Susy Srihandayani; Azwan Azis; Wan Ramli (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Development in areas with soft soil conditions, such as Dumai, faces technical challenges related to low carrying capacity and high land subsidence. Lightweight and economical foundation solutions are an urgent need, especially for small and medium-scale structures. This study aims to validate the axial bearing capacity of PVC poles in soft clay soils using two approaches: the experimental interpretation of the Mazurkiewicz method and the theoretical approach of the Meyerhof method. Laboratory tests were performed on four variations of PVC pipe diameters (2